Increasing incidence of primary shoulder arthroplasty in Finland - a nationwide registry study - Jenni N. E. Harjula; Juha Paloneva; Jaason Haapakoski; Juha Kukkonen; Ville Äärimaa; Finnish Shoulder Arthroplasty Registry Group (BMC, 2022)
Background: The incidence of shoulder arthroplasties is reportedly increasing and the types of arthroplasty are changing. The purpose of this study was to investigate the incidence of primary shoulder arthroplasty in Finland.Methods: We analyzed nationwide data from the Finnish Arthroplasty Register (FAR) and the Finnish National Hospital Discharge Register (NHDR) during time period 2004-2015. The primary outcome variable was the incidence of shoulder arthroplasty per 100,000 person-years stratified by age, sex and year of surgery. The secondary outcome variables were surgical indication, arthroplasty type and prosthesis model.Results: The number of primary shoulder arthroplasties was 7504 (women = 4878, men = 2625). The rate of operations increased from 6 to 15 per 100,000 person-years among men, and 11 to 26 per 100,000 person-years among women. The indication for arthroplasty was osteoarthritis in 56%, acute fracture in 21%, inflammatory arthritis in 13%, and rotator cuff arthropathy in 4% of the cases. Hemiarthroplasties accounted for 66%, total shoulder arthroplasties 8%, and reverse shoulder arthroplasties 12% of the cases, 14% of the cases was missing. During the 12-year study period the incidence of hemiarthroplasties decreased by 23% and the number of total shoulder and reverse shoulder arthroplasty increased by 500 and 4500%, respectively.Conclusions: The incidence of primary shoulder arthroplasty has increased by 160% during the study period in Finland. The incidence of hemiarthroplasties decreased while total and reverse shoulder arthroplasties increased.